(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: To determine the prevalence of concurrent hypertension and dyslipidemia among individuals with type 2 diabetes mellitus (T2DM) and to evaluate the impact of demographics, clinical, and lifestyle factors on this coexistence. Methodology: A cross-sectional study was carried out at the Diabetes Clinic, Medical Unit III, JPMC, between July 2023 and March 2024. A total of 248 adults with T2DM were enrolled using convenience sampling. Demographic data, along with duration of diabetes, family history, lifestyle habits, body mass index (BMI), waist circumference, and blood pressure, were recorded. Laboratory assessments included fasting blood glucose (FBG), glycated haemoglobin (HbA1c), detailed lipid profile, and liver enzymes. Hypertension and dyslipidemia were classified according to standard diagnostic criteria. Data were analysed using SPSS version 25, applying descriptive statistics and chi-square tests, with significance set at p < 0.05. Results: Out of 248 type 2 diabetic patients, 150 (60.5%) had coexisting hypertension and dyslipidemia (lipitension). The prevalence increased with age, reaching 71.3% in patients aged 60+ years. Females had a higher prevalence (45.2%) compared to males (15.3). A sedentary lifestyle was significantly associated with lipitension (50.4% vs. 10.1%, p = 0.01), and longer diabetes duration also increased the prevalence (70.0% for >10 years, p = 0.04). Family history of hypertension (66.0%, p = 0.03) and dyslipidemia (70.1%, p = 0.04) further increased the likelihood of lipitension. Conclusion: The coexistence of hypertension and dyslipidemia is common in T2DM, particularly in older, sedentary patients with prolonged disease duration or positive family history. Early detection and risk-factor modification are essential to reduce cardiovascular complications.